P292 Validation Of The Stop-bang Questionnaire As A Screening Tool For Sleep Apnoea In Patients Undergoing Ablation For Paroxysmal Atrial Fibrillation. (10th November 2014) - Pittman, MA; Mason, M; Packer, D; Chadwick, R; Clutterbuck-James, A; Fynn, S; Quinnell, TG
Abstract : Background: Patients with treated obstructive sleep apnoea have a greater chance of treatment success compared to those untreated, when undergoing ablation for atrial fibrillation (AF) (Patel et al 2010). The STOP-BANG questionnaire has previously been validated as a screening tool for detecting sleep apnoea in surgical patients (Chung et al 2008), but has not been validated for use in AF patients. We present the results from a study investigating its predictive value in AF patients. Methods: Patients with paroxysmal AF undergoing ablation were approached. Those with previously diagnosed sleep apnoea were excluded. Participants completed the STOP-BANG questionnaire and underwent overnight oximetry. Of 228 patients approached, 101 participated. Sleep apnoea was defined as a 4% desaturation index of >5 per hour, and participants were reviewed by an experienced sleep physician to determine if treatment with continuous positive airway pressure (CPAP) was necessary. Results: Of the 101 patients screened, 36 had sleep apnoea, and 13 were offered treatment with CPAP. The STOP-BANG questionnaire (with a cut off of 3 or more out of 8 questions answered positively considered 'high risk') had a sensitivity of 97.2% and a specificity of 43.1% for detecting sleep apnoea in this group. The STOP questions alone (with a cut off of 2 or more out of 4 considered 'high risk') had a sensitivity of 75.0% and a specificity of 63.1%, however the sensitivity was 100% and specificity 56.8% for predicting the need for CPAP. Conclusion: There is a high prevalence of undiagnosed sleep apnoea in this patient group. The STOP-BANG questionnaire has a high sensitivity for detecting sleep apnoea in AF patients. The STOP questions alone have a high sensitivity for detecting sleep apnoea requiring treatment. References: Patel D, Mohanty P, Di Biase L, et al . Circ Arrhythm Electrophysiol. 2010 Oct;3(5):445-51 Chung F, Yegneswaran B, Liao P, et al . Anesthesiology. 2008 May;108(5):812-21